(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
"In the present work, optical constants have been studied for pure and titanium dioxide (TiO2) doped iron oxide (Fe2O3) thin films with different titanium dioxide dopant concentrations (1, 3 and 5 %) prepared by chemical spray pyrolysis technique on glass substrates. The optical properties of the films, which were prepared with a thickness of (260±10) nm, have been determined by using Shimadzu spectrophotometer, the optical transmittance measurements in the spectral region from (500- 1100) nm. Direct energy gap for (Fe2O3) equal (2.01) eV, it increases with increasing of TiO2%. The optical constants such as refractive index, extinction coefficient and dielectric constants have been calculated for all prepared films. The results show that all optical constants decrease with the increasing of dopant ratios."